Desarrollo de la motricidad fina en niños de 2 a 3 años, provenientes de hogares disfuncionales - Diaz Gaona, Amparo Del Rocio (2018)
The presentation of this project itself is based on a previous inquiry into the use of several scientific articles by duly recognized authors, which theoretically allowed us to provide clear ideas on the topic of this research that is fine motor development in children from 2 to 3 years from dysfunctional homes, in order to make known the phase of fine motor development in which the child is, in order to fulfill that process of development of skills and abilities according to their age and obtain the same level of learning as that of other children, this way it is necessary to consider the stimulation provided to the child will allow not only strengthen the fine motor, but the development of other stimuli, such as the use of eyes, hands , the face, motor movements, allowing development the activation of muscles within this process is demonstrated through processes coordinated, harmonic and continuous; In this way, based on an observation sheet, and interview with the parents, it was possible to know that the children do need the help of their family, and to be aware of that process and so the infant can not present problems later in its growth. , as a result of which the relatives of that go through very difficult situations as it is of dysfunctional homes, the same ones that are affected are the small ones of house because due to great problems that happens each one of the members of the household is neglected of the small because many times they are not under the care of them because many parents work outside the home and leave their children with other people for their care, that's why in order to strengthen movements of fingers, hands and wrists, with the use of appropriate materials such as painting, funky, etc, that motivate them to achieve an achievement in their motor skills and skills that are only acquired during their process of evolutionary growth, it is a slow process, the same one that should be given to the infant little by little allowing him to achieve this achievement, will allow you later not to have problems in the writing, but will help you to master and direct the pencil well, for this purpose a proposal was proposed with the pedagogical guide theme to develop fine motor skills based on exercises: painting, tearing, balance, etc., in order to strengthen fine motor skills, through plastic expressions such as trimming, drawing, etc., activities that draw attention to their use and development. roll, the same ones that will allow later not to have shortcomings but correct and that will allow a significant learning, but in addition a manual oculo maturation is needed and a psychological process by which the child perceives his hands as usable instruments to mold, transform, reproduce, catch, throw, and the main thing to grow with bonds of love, fraternity on the part of their parents reaching the full development of the child.